Novel colorimetric method overcoming phosphorus interference during trace arsenic analysis in soil solution - Punamiya, Pravin; Sarkar, Dibyendu; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2008)
A sensitive (method detection limit, 2.0 μg As L-1) colorimetric determination of trace As(v) and As(iii) concentrations in the presence of soluble phosphorus (P) concentrations in soil/water extracts is presented. The proposed method modifies the malachite green method (MG) originally developed for P in soil and water. Our method relies upon the finding that As(iii) and As(v) do not develop the green color during P analysis using the MG method. When an optimum concentration of ascorbic acid (AA) is added to a sample containing up to 15 times P > As (μM) concentrations, the final sample absorbance due to P will be equal to that of As(v) molecules. The soluble As concentration can then be quantified by the concentration difference between the mixed oxyanion (As + P) absorbance (proposed method) and the MG method absorbance that measures only P. Our method is miniaturized using a 96-well microplate UV-VIS reader that utilizes minute reagent and sample volumes (120 and 200 μL sample-1, respectively), thus, minimizing waste and offering flexibility in the field. Our method was tested in a suite of As-contaminated soils that successfully measured both As and P in soil water extracts and total digests. Mean% As recoveries ranged between 84 and 117%, corroborating data obtained with high-resolution inductively-coupled plasma mass-spectrometry. The performance of the proposed colorimetric As method was unaffected by the presence of Cu, Zn, Pb, Ni, Fe, Al, Si, and Cr in both neutral and highly-acidic (ca. pH 2) soil extracts. Data from this study provide the proof of concept towards creating a field-deployable, portable As kit.
Keywords: Aluminum; Arsenic; Ascorbic acid; Chromium; Copper; Iron; Lead; Malachite green; Nickel; Phosphorus; Silicon; Soil water; Zinc